O PIBID E A FORMAÇÃO DOCENTE - Ames, William Luís; Menegazzi, Kemely Pavani; Chagas, Aloma Gabriela Prestes; Possani, Taíse Neves (Salão do Conhecimento, 2019)
Trabalho desenvolvido junto às atividades da Bolsa de Iniciação à docência – PIBID UNIJUI